2018
DOI: 10.1111/his.13723
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 and IDO expression in cervical and vulvar invasive and intraepithelial squamous neoplasias: implications for combination immunotherapy

Abstract: In summary, IDO and PD-L1 co-expression is common in cervical SCCs and, to a lesser extent, vulvar SCCs. These data suggest a role for combination immunotherapy in a subset of cervical SCCs as well as select vulvar SCCs. Expression for both markers is less common in intraepithelial lesions, providing no strong support for this form of immunotherapy in the absence of invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“…This result is consistent with the finding of Sznurkowski et al that show 96.05% of VSCC mostly diffuse IDO expression in Poland population . However, two other studies have shown a lower IDO expression in the Netherlands population (50.4%) and in United States (30%) . This inconsistency may be because of the ethnicity and/or the used anti‐IDO antibody that is different in de Jong study (Monoclonal antibody, clone 10.1; Millipore, Chemicon), and in Chinn study (Polyclonal antibody, HPA 023072, Sigma Prestige).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the finding of Sznurkowski et al that show 96.05% of VSCC mostly diffuse IDO expression in Poland population . However, two other studies have shown a lower IDO expression in the Netherlands population (50.4%) and in United States (30%) . This inconsistency may be because of the ethnicity and/or the used anti‐IDO antibody that is different in de Jong study (Monoclonal antibody, clone 10.1; Millipore, Chemicon), and in Chinn study (Polyclonal antibody, HPA 023072, Sigma Prestige).…”
Section: Discussionsupporting
confidence: 92%
“…50 However, two other studies have shown a lower IDO expression in the Netherlands population (50.4%) 4 and in United States (30%). 51 This inconsistency may be because of the ethnicity and/or the used anti-IDO antibody that is different in de Jong study (Monoclonal antibody, clone 10.1; Millipore, Chemicon), and in Chinn study (Polyclonal antibody, HPA 023072, Sigma Prestige). This increase of IDO might have effects on CTL and NK cells by the decrease of tryptophan level and the increase of kynurenine in the vulvar microenvironment, reducing their activation or inducing their apoptosis, and on LT regulators by their activation 16,21,52 (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…IDO1 is known to induce immune suppression in local tumor environment by promoting the differentiation of regulatory T cell and inhibiting the function of effector T cells [19]. And IDO1 is commonly co-expressed with programmed death ligand 1(PD-L1) in cervical squamous carcinomas [20].…”
Section: Discussionmentioning
confidence: 99%
“…Vulvar cancer is one of the less frequently diagnosed gynecological cancers, with 6120 new cases predicted to be encountered in the US in 2020 and 1350 deaths expected due to this disease (Table 1) [1]. PD-L1 is reported to be expressed in most vulva squamous cell carcinoma [6,142,143], even though the significance of this parameter is not yet well understood. Clinical trials for vulvar and vaginal cancer are often part of basket studies of HPV-associated cancers (CheckMate 358).…”
Section: Cervical and Other Female Gynecologic Cancersmentioning
confidence: 99%